What do descriptive representatives describe? Minority representative claims and the limits of shape-shifting. (October 2019) - Bajpai, Rochana
In contemporary debates on diversity, minorities are characterized mostly in terms of their cultural difference from the majority. Scholars have tended to focus on the role of minority representatives as advocates of their group interests in legislative assemblies. Focussing on election campaigns, this article examines how minority representatives reach out to a mixed electorate, comprising voters of both minority and non-minority backgrounds. Bringing together two distinct strands of the recent representative turn in political theory, theories of descriptive representation and constructivist theories of representation, I argue the following. First the influential contrast between the politics of presence and the politics of ideas underestimates the multi-dimensional and dynamic nature of minority identities as well as the respects in which minority representation is conditioned and constrained by the politics of ideas associated with party competition. Second, while Saward's notion of shape-shifting representation is promising for illuminating the multiple positionalities of minority representatives and the dynamic character of descriptive representation, its current formulation does not offer adequate criteria for operationalizing shape-shifting and evaluating its democratic character. Third, ethnographic approaches have an important role to play in countering the tendency in normative debates for the reification of minority identities and the idealization of the democratic role of political parties. These arguments are established through a comparative case study of the representative claims of BJP MPs of Dalit (Scheduled Caste) and Muslim backgrounds during the 2014 Indian national election campaign.